Ora sive labora? - Wojciech Zyzak (Polonia Sacra)
Reflecting upon the relationship between prayer and work the Author of the article refers to the well known Benedictine formula “ora et labora”. It is to emphasize that both, prayer and work should find a proper place in a Christian’s life. Since the accents can be optional, the Author claims that within the incarnational spirituality the lay Christians may identify themselves rather with the reverse order of this formula: “labora et ora”. However we should never separate these two options neither put them in the form: “ora sive labora”, which has been provocatively used in the title of this paper. The true masterpiece of the lays’ life is to perform duties of Martha in the spirit of Mary, which does not necessarily mean the focus on God during one’s work. It’s often even impossible. The work itself done professionally and with the proper intention can become a form of ontological worship, unless one would neglect the prayer itself. Nourished with prayer the theologal love makes all activities a form of adoration of God, transforming life into the constant prayer.